Konservasi Budaya Lokal Banyuwangi Melalui Museum Blambangan Berbasis Banyuwangi Ethno Carnival - Ishardhi, R. Dravendy Marta (PMIH Untag Semarang, 2025)
Banyuwangi is known for its rich local culture and tourism that continues to grow rapidly. Over the past few years, the number of tourist visits to Banyuwangi has increased significantly, mainly thanks to the Banyuwangi Festival, an annual event organized by the Regional Government and local communities. The authenticity of local culture in Banyuwangi is maintained, thanks to the efforts of the community who continue to preserve their local wisdom. This paper aims to analyze the strategy of using the Blambangan Museum in Banyuwangi as a means of cultural conservation and as a forum to preserve the cultural arts displayed in the Banyuwangi Ethno Carnival. The research methods used include direct data collection through observation, interviews, literature studies, and document analysis, with the presentation of results in descriptive form. The research shows several important things: first, many works of art and culture produced in the Banyuwangi Ethno Carnival (BEC) need to be identified and maintained properly; second, the need for museum-based educational facilities to support cultural tourism in Banyuwangi Regency; and third, the Banyuwangi Museum has the potential to become an alternative education-based tourism destination, which can further increase the number of tourists who come to this area.